Cytotoxic T lymphocytes to Plasmodium falciparum epitopes in an area of intense and perennial transmission in Tanzania. - Lalvani, A; Hurt, N; Aidoo, M; Kibatala, P; Tanner, M; Hill, A (1996)
Studies in The Gambia have provided indirect evidence that cytotoxic T lymphocytes (CTL) play a protective role against malaria in humans and recently, using allele-specific HLA class I peptide motifs, several peptide epitopes for CTL in four pre-erythrocytic Plasmodium falciparum antigens have been identified in naturally exposed Gambians. However, CTL levels were low, suggesting that boosting these low levels by immunization might provide substantial protection. In the Kilombero valley of Tanzania, malaria transmission is holoendemic and 300 times more intense than in The Gambia. We report here that several of the epitopes identified in The Gambia are also recognized in naturally exposed, partially immune Tanzanian adults and that levels of CTL are similar to or slightly higher than in Gambian subjects, despite the much higher inoculation rate. We report a new HLA-A2.1-restricted epitope from the thrombospondin-related anonymous protein (TRAP) and we demonstrate that peptide epitopes in TRAP are naturally processed for recognition by CTL from naturally exposed humans. The common allele of a variable HLA-B7-restricted epitope in the circumsporozoite protein behaved as an altered peptide ligand (APL) with respect to CTL cognate for a rarer allelic variant of this epitope, suggesting that APL antagonism may occur in natural CTL responses to P. falciparum. The moderate levels of CTL observed, even in this area of intense malaria transmission, points to the need to assess candidate vaccines aimed at increasing CTL levels.